2010
DOI: 10.1074/jbc.m109.044180
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure and Computational Analyses Provide Insights into the Catalytic Mechanism of 2,4-Diacetylphloroglucinol Hydrolase PhlG from Pseudomonas fluorescens

Abstract: 2,4-Diacetylphloroglucinol hydrolase PhlG from Pseudomonas fluorescens catalyzes hydrolytic carbon-carbon (C-C) bond cleavage of the antibiotic 2,4-diacetylphloroglucinol to form monoacetylphloroglucinol, a rare class of reactions in chemistry and biochemistry. To investigate the catalytic mechanism of this enzyme, we determined the three-dimensional structure of PhlG at 2.0 Å resolution using x-ray crystallography and MAD methods. The overall structure includes a small N-terminal domain mainly involved in dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…The threedimensional structure of His 6 -PhlG indicates that these amino acid residues are located in different positions than the catalytic site of the enzyme. 7) PhlG was purified from E. coli XL1-Blue MRF 0 carrying pUHH1.3. Table 1 summarizes the purification procedure.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The threedimensional structure of His 6 -PhlG indicates that these amino acid residues are located in different positions than the catalytic site of the enzyme. 7) PhlG was purified from E. coli XL1-Blue MRF 0 carrying pUHH1.3. Table 1 summarizes the purification procedure.…”
mentioning
confidence: 99%
“…It lost about half of its activity when incubated at 47 C for 20 min, and was completely inactivated at 55 C. The kinetic constants, K m and k cat , were determined by double reciprocal plot to be 24 mM and 5. of PhlG-His 6 of P. fluorescens CHA0 indicated that Histagged PhlG had a markedly higher K m value than PhlG. 6,7) This might have been due to the presence of an extra peptide chain at the N-terminus in His-tagged PhlG. MAPG competitively inhibited the enzyme (K i ¼ 87 mM), while 2-hydroxy-and 4-hydroxyacetophenone were ineffective.…”
mentioning
confidence: 99%
See 3 more Smart Citations